2015
DOI: 10.1016/j.chiabu.2015.08.002
|View full text |Cite
|
Sign up to set email alerts
|

The relationships between therapeutic alliance and internalizing and externalizing symptoms in Trauma-Focused Cognitive Behavioral Therapy

Abstract: Therapeutic alliance has been considered an important factor in child psychotherapy and is consistently associated with positive outcomes. Nevertheless, research on alliance in the context of child trauma therapy is very scarce. This study examined the relationships between child therapeutic alliance and psychopathology in an empirically supported child trauma therapy model designed to address issues related to trauma with children and their caregivers. Specifically, we examined the extent to which the child's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 64 publications
0
25
0
1
Order By: Relevance
“…Therapists can also promote agency and controllability by giving explicit choices to young people and fostering collaborative decision-making, e.g. about the extent and timing of parental involvement [54][55].…”
Section: Discussionmentioning
confidence: 99%
“…Therapists can also promote agency and controllability by giving explicit choices to young people and fostering collaborative decision-making, e.g. about the extent and timing of parental involvement [54][55].…”
Section: Discussionmentioning
confidence: 99%
“…Frequently researched therapist variables are the therapists’ theoretical background/orientation (Anderson, Ogles, Patterson, Lambert, & Vermeersch, 2009 ; Berglar et al, 2016 ; Okiishi et al, 2006 ), professional interpersonal skills or self-rated professional characteristics (Heinonen & Nissen-Lie, 2019 ), therapists’ alliance-building behaviours (Jungbluth & Shirk, 2009 ; Ovenstad, Ormhaug, Shirk, & Jensen, 2020 ), professional experience (e.g. years of experience doing therapy; Huppert et al, 2001 ; Turner, Nicholson, & Sanders, 2011 ), age (Anderson et al, 2009 ; Schauenburg, Dinger, & Strack, 2005 ) and gender (Shiner, Westgate, Harik, Watts, & Schnurr, 2017 ; Zorzella, Muller, & Cribbie, 2015 ). However, these studies have investigated very heterogeneous samples and the results regarding the impact of the therapist variables on outcome are highly contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…In TF-CBT, the only therapist-related factor that has been researched to any extent is the working alliance between patient, therapist and caregiver (Kirsch, Keller, Tutus, & Goldbeck, 2018 ). The alliance between patient and therapist has been proven to have a significant impact on therapy outcome (Ormhaug, Jensen, Wentzel-Larsen, & Shirk, 2014 ) and female therapists seem to have higher rates of alliance with their patients (Zorzella et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…In children and adolescents, slightly smaller effects of alliance are reported ( r = 0.14, [ 25 ]; r = 0.22, [ 26 ]), and some studies fail to demonstrate the alliance-outcome link [ 27 ]. With regard to children and adolescents suffering from PTSS, two randomized controlled trials (RCTs) found positive effects of therapeutic alliance on symptom reduction, especially on internalizing symptoms in the TF-CBT condition [ 8 , 28 ], whereas another RCT for prolonged exposure in adolescent girls did not find any link between alliance and outcome [ 29 ]. Possibly, stronger alliance enhances collaboration and engagement in TF-CBT tasks, which leads to higher symptom reduction, but this was not investigated in children and adolescents with PTSS so far.…”
Section: Introductionmentioning
confidence: 99%
“…Most recent investigations of common factors in children and adolescents with PTSD focused on working alliance, neglecting TE or a more integrative model of several common factors. Most of all, recent TF-CBT studies [ 8 , 28 , 29 ] did not include caregivers’ rating of common factors, therefore might underestimate their important role in symptom reduction. The current study aims to fill this gap in research on TE in children and adolescents with PTSS and their caregivers.…”
Section: Introductionmentioning
confidence: 99%